Comparative differences in the risk of major gastrointestinal bleeding among different direct oral anticoagulants: An updated traditional and Bayesian network meta-analysis - Chen, Xiuehui; Wang, Lili; Li, Huijun; Huang, Weichao; Zhao, Lingyue; Guo, Wenqin (Frontiers in Pharmacology, 2023)
Background: The most favorable gastrointestinal (GI) bleeding safety profile among different types of direct oral anticoagulants (DOACs) remains controversial. This meta-analysis includes the latest studies and aims to compare GI bleeding risk associated with the use of various DOACs. Methods: PubMed, Cochrane library, and clinicaltrial.gov were searched. Randomized control trials (RCTs) evaluating the safety of DOACs were identified. The primary endpoint assessed was major GI bleeding. Results: A total of 37 RCTs were included in the analyses. Based on the traditional meta-analysis, the major GI bleeding risk was different among various DOACs (interactive p-value <.10). Network meta-analysis findings showed that no DOACs increased the risk of major GI bleeding compared with conventional therapy. Furthermore, a 10 mg daily administration of apixaban reduced the major GI bleeding risk more than daily doses of 60 mg edoxaban, ≥15 mg rivaroxaban, and 300 mg dabigatran etexilate. No difference was observed between daily doses of 300 mg dabigatran etexilate, 60 mg edoxaban, and ≥15 mg rivaroxaban. The major GI bleeding risk associated with 30 mg daily dose of edoxaban was lower than with 10 mg daily rivaroxaban, and no differences between daily 5 mg apixaban, 30 mg edoxaban, and 220 mg dabigatran etexilate were observed. Conclusion: Differences in the major GI bleeding risk were observed when various DOACs were compared. Among standard-dose DOACs, apixaban was associated with the lowest degree of major GI risk. Among low-dose DOACs, edoxaban was associated with a lower major GI bleeding risk than rivaroxaban.